Relationship Between Ultrasonographic and Biochemical Markers of Tubal Ectopic Pregnancy and Success of Subsequent Management. (20th April 2018) - Nadim, Batool; Lu, Chuan; Infante, Fernando; Reid, Shannon; Condous, George
Abstract : Objectives: To determine whether there is an association between morphologic types of tubal ectopic pregnancy (EP), 0‐hour human chorionic gonadotropin (hCG) levels, and subsequent management success. Methods: We conducted a prospective study (November 2006–December 2015). Women had a diagnosis of EP by transvaginal ultrasonography if they had an inhomogeneous mass adjacent to the ovary and moving separately from it ("blob" sign), a mass with a hyperechoic ring around the gestational sac ("bagel" sign), or a gestational sac with an embryonic pole with or without a yolk sac with or without cardiac activity. The morphologic type, EP size, and 0‐hour hCG level were analyzed. A multivariate analysis determined any correlation between these variables and nonsurgical management success. Results: A total of 7350 consecutive women underwent transvaginal ultrasonography, of whom 301 (4.2%) had a diagnosis of tubal EP; 181 (60.1%) had the blob sign; 90 (29.9%) had the bagel sign; and 23 (7.6%) were noted to have an embryo (14 viable and 9 nonviable). Eighty‐three of 301(27.5%) women had expectant management; 67 of 301(22.2%) were given methotrexate; and 151 of 301 (50%) had surgery. Success rates for the groups were 77%, 75%, and 100%, respectively. No difference between the morphologic type and success rate of treatment was noted. Although there was a significant correlation between the EP mass size and 0‐hour hCG level, the mass size itself was not correlated with the success rate of either medical or expectant management. Overall higher 0‐hour hCG levels were associated with management failure. In the expectant group, median hCG level for failure was 589 IU/L versus 366 IU/L for success, whereas in the medical group, the median for failure was 1244 IU/L versus 7629 IU/L for success. Conclusions: There is no significant correlation between the morphologic type and size of EP with a nonsurgical management outcome. A likely successful outcome is related to a lower level of serum hCG at presentation.